Video in social science research functions and forms - Haw, Kaye; Hadfield, Mark. (London Routledge, 2011)
Covering issues such as technical and aesthetic considerations in objective research this book is a practical research tool for the digital age that shows, how, why and when video could and should be used in social science research.
Forms and functions -- Video used in extractive mode -- Using video in a reflective mode -- Video as projection and provocation -- Video that generates participation -- Video, voice and articulation -- Video and your research : function and forms -- Video and your research : from methodology to methods.
Keywords: Social sciences -- Research -- Audio-visual aids